The Impact of Parental Incarceration on Psychopathy, Crime, and Prison Violence in Women - Thomson, Nicholas D. (International journal of offender therapy and comparative criminology, 2020)
There is a growing interest in understanding the consequences of parental incarceration. Unfortunately, research exploring the long-term criminological and personality effects in female offspring is limited, particularly among second-generation female offenders. In a sample of 170 female offenders, we first assessed the correlations between psychopathy facets, prison violence, and types of crime. Next, we tested the association between childhood exposure to paternal and/or maternal incarceration on adulthood psychopathic traits, criminal offending, and prospective prison violence over 12 months. Correlations showed the interpersonal facet was positively correlated with fraud-related crime and prison violence. The affective facet was positively correlated with violent crime and prison violence. The behavioral facet was associated with prison violence and drug-related crime. Multinomial logistic regressions showed higher interpersonal facet scores were associated with an increased likelihood of having experienced paternal incarceration. Higher affective facet scores, violent crime, and prison violence were associated with an increased likelihood of having experienced maternal incarceration, regardless of if the father had been incarcerated or not. It is evident that having any parent incarcerated during childhood can be harmful to daughters; however, our findings dovetail with prior research showing that maternal incarceration leads to more detrimental outcomes for women.